Two systems drive attention to rewards - Kovach, Christopher K.; Sutterer, Matthew J.; Rushia, Sara N.; Teriakidis, Adrianna; Jenison, Rick L. (Frontiers in Psychology, 2014)
How options are framed can dramatically influence choice preference. While salience of information plays a central role in this effect, precisely how it is mediated by attentional processes remains unknown. Current models assume a simple relationship between attention and choice, according to which attention should uniformly bias preference towards the attended item over the whole time-course of a decision between similarly valued items. To test this prediction we considered how framing alters attention during a simple choice between two options, using eye movements as a sensitive online measure of attention. In one condition participants selected the less preferred item to discard and in the other, the more preferred item to keep. We replicated the well-known observation that gaze gravitates towards the item ultimately selected, but did not observe the effect to be uniform over time. Instead, we found evidence for distinct early and late processes that guide attention according to preference in the first case and task demands in the second. We conclude that multiple time-dependent processes govern attention during choice, and that these may contribute to framing effects in different ways.